A sharable platform for e-learning based on cloud computing architecture. (1st January 2013) - Wang, Chun-Chia
Over the internet, e-learning has speeded up the knowledge transfer without restrictions on time and space in recent years. In order to achieve the goal of knowledge sharing and reusing interactively, lots of available e-learning standards have been adapted to complete the purpose. Normally, learning objects meeting these standards are sharable with other e-learning platforms. Most e-learning platforms, however, are unable to share learning objects directly on the internet. The characteristics of cloud computing provide a promising infrastructure to compute and store resources as services. Hence, this paper introduces cloud computing into an e-learning platform to allow the integration of different e-learning standards to enhance interoperability of learning objects. Besides, an automated standard transformation algorithm is described and implemented on a cloud environment. The proposed approach reveals an expected result that reduces, at least, 2, 500 ms for the access of learning content with heterogeneous packaging formats. Therefore, by combining the characteristics of e-learning and approach of cloud computing, educators have not to re-construct learning objects to satisfy e-learning environments developed from different e-learning standards.